Rozner, Sarah (audio interview #7 of 20) - Rozner, Sarah (b. 1892 - d. 12/?/1980); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the fifteenth interview with Sarah Rozner conducted in her home. She had not been feeling well the day prior to the interview and spent the entire day in bed. However, she seemed well during the interview. Although the interview was going to focus on her European trip and her experiences with labor people in Europe, over lunch we got into a discussion regarding the Haymarket Riot, since the previous Sunday was the anniversary of that event. TOPICS - opinions on anarchism, communism, the Wobblies, and capitalism; treatment of women in each of these systems; women's status; and view of union today as an organ of a capitalistic society;meeting Angelica Balabanoff; women's status; feminist consciousness; friendships; background factors in making her such a strong and tough woman; 11/13/1973